ChemInform Abstract: [Mn12O12(O2CMe)12 (NO3)4(H2O)4]: Facile Synthesis of a New Type of Mn12 Complex. Issue 24 (June 2015) - Thuijs, Annaliese E.; Christou, George; Abboud, Khalil A.
Abstract: The entitled Mn complex is obtained from the filtrate of an 8:4 molar mixture of Mn(O‐Ac)2 and CAN in warm MeNO2 with an excess of AcOH (3 d, 40 % yield).